2004
DOI: 10.1023/b:clin.0000017168.83616.d0
|View full text |Cite
|
Sign up to set email alerts
|

Levels of expression of endothelial markers specific to tumour-associated endothelial cells and their correlation with prognosis in patients with breast cancer

Abstract: Tumour endothelial markers (TEMs) are a newly discovered family of endothelial markers associated with tumour specific angiogenesis. This study sought to examine the levels of expression for TEMs in human breast cancer. Breast cancer tissues (n = 120) together with normal background tissues (n = 33) were obtained after surgery. RNA was extracted from frozen sections for gene amplification. The expression of TEMs was assessed using RT-PCR and the quantity of their transcripts was determined using real-time-quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 26 publications
4
77
1
1
Order By: Relevance
“…Although PLXDC2 is usually upregulated with PLXDC1 in stromal endothelial cells of several tumors, such as colorectal cancer (25), it does not appear to govern endothelial cell morphogenesis in these tumors like PLXDC1 (25). Instead, PLXDC2 participates in apoptosis and cellcycle arrest (26) and is also associated with poor outcomes, a worse prognosis, and lymph node metastasis in breast cancer (27). Regardless of the increasing association of this gene with tumor behavior, its function and interactions have not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although PLXDC2 is usually upregulated with PLXDC1 in stromal endothelial cells of several tumors, such as colorectal cancer (25), it does not appear to govern endothelial cell morphogenesis in these tumors like PLXDC1 (25). Instead, PLXDC2 participates in apoptosis and cellcycle arrest (26) and is also associated with poor outcomes, a worse prognosis, and lymph node metastasis in breast cancer (27). Regardless of the increasing association of this gene with tumor behavior, its function and interactions have not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms that control endosialin expression have remained elusive (Rettig et al, 1992;Brady et al, 2004;Davies et al, 2004;Madden et al, 2004;Dolznig et al, 2005;MacFadyen et al, 2005;Huber et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have confirmed that endosialin is upregulated in blood vessels and activated stromal fibroblasts in human colorectal, brain and breast tumours as well as in mouse xenograft models (Carson-Walter et al, 2001;Brady et al, 2004;Davies et al, 2004;Madden et al, 2004;Dolznig et al, 2005;MacFadyen et al, 2005MacFadyen et al, , 2007Huber et al, 2006;Rupp et al, 2006). Endosialin expression is restricted to capillaries and shows a heterogeneous pattern typical for molecules involved in vascular reorganisation.…”
mentioning
confidence: 92%
“…This does not diminish their potential importance as tumor vascular markers or therapeutic targets in a subset of patients. Importantly, this is the case for tumor vascular markers that have already been validated and are currently being developed as therapeutic targets, e.g., TEM1, 34 for which therapeutic antibodies are already under early phase clinical testing. Ideally, for the purpose of tumor detection, development of molecular imaging tools should focus on genes that are highly expressed in most EOC tumors.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%